Development of thulium-doped and co-doped fiber lasers using graphene and graphene related saturable absorber / Hanafiah Shamsudin - Hanafiah , Shamsudin (2017)
Two-micron pulsed fiber lasers offer numerous applications in various fields such as high-precision material processing, bio-medicine and ranging. This thesis focuses on the development of fiber lasers that emit longer wavelength beams utilizing thulium-doped fiber (TDF), thulium-ytterbium co-doped fiber (TYDF) and thulium-holmium co-doped fiber (THDF) as the gain medium in conjunction with a carbon-based saturable absorber (SA). Various SA based on graphite, carbon nanotubes and graphene were fabricated for use in generating both Q-switching and mode-locking pulse train in 2-micron region. TDF lasers (TDFLs) operating in multi-wavelength, Q-switching and mode-locking modes have been successfully demonstrated. For instance, the mode-locked TDFL operating at 1901.6 nm was demonstrated using a graphene oxide (GO) paper as SA. It generates 82.4 MHz pulse train with the estimated pulse width of 12.66 ps, and the pulse energy of 83.1 pJ at the 1552 nm pump power of 1052 mW. The TYDF laser (TYDFL) provides an efficient lasing at 1950 nm region based on energy transfer from ytterbium to thulium ions. A mode-locked TYDFL is also successfully demonstrated using a GO-based SA. The laser operates at 1942.0 nm with a threshold pump power as low as 1.8 W, a repetition rate of 22.32 MHz and calculated pulse duration of 1.1 ns. Continuous wave (CW), Q-switched and mode-locked THDF laser (THDFL) have also been successfully demonstrated using THDF as the gain medium in conjunction with 1552 nm pumping. The CW THDFL operates at around 1980 nm region with an efficiency of 5.78 % with the use of 5 m long gain medium due to Ho3+ transition (5I7  5I8). Q-switched and mode-locked THDFL were realized using GO embedded in polyvinyl alcohol (PVA) film as a passive SA. The self-started Q-switching pulse train was realized with the repetition rate, pulse width, output power, and pulse energy of 54.43 kHz, 2.44 μs, 8 mW, and 0.146 nJ, respectively at the maximum pump power of 1151 mW. By adding 10 m long highly nonlinear scandium doped fiber (ScDF) inside the similar THDFL cavity, the laser can be transformed into the mode-locking mode with the repetition rate of 9 MHz and an estimated minimum possible pulse width of 10.29 ps.